A Study of Residents’ Satisfaction with the Service Quality of the ABC Condominium Juristic Person - ค้าคล่อง พนิดา; วงษ์เล็ก ภูษิตย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to study and compare residents’ satisfaction with the service quality of the juristic person of ABC Condominium, classified by personal factors; gender, age, occupation, and income. The sample consisted of 242 residents of ABC Condominium, selected through simple random sampling. The research instrument used for data collection was a questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.67-1, and the overall reliability coefficient was 0.99. The statistics used for data analysis included percentage, mean, and standard deviation, hypotheses were tested using t-test and One-Way Analysis of Variance (One-Way ANOVA), with the level of statistical significance set at 0.05. The results of the research revealed that: 1) The residents were satisfied toward the service quality of the juristic person of ABC Condominium, overall and all aspects were at a high level. The highest satisfaction was the assurance; the subordinate satisfactions were the empathy, the reliability, the tangibles, and the responsiveness. 2) The residents who were different gender, age, occupation, and income satisfied toward service quality of the juristic person of ABC Condominium, overall, showed the not difference at the statistical significance level of 0.05.